COMMODIFICATION OF RELIGION IN THE QURANIC PERSPECTIVE (A STUDY AT KAMPUNG KERAMAT, BABUSSALAM, NORTH SUMATERA) - Husna, Nurul; Manik, Hasanuddin (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2023)
Religion, on the one hand, is something sacred, but on the other hand, there is a phenomenon wherein it is used to earn profits for business. It appears that religion has turned into a marketing point that alters the sacred nature of the essence of religion itself, with religious symbols serving as a way to attract consumers' interest in purchasing goods. This study describes the phenomenon of religious commodification in light of the Quran. The qualitative research method was used in the present study. Primary data were collected from business owners near Tuan Guru Babussalam Langkat's graveyard area. The field research data were analyzed from the viewpoint of the Qur'an. The findings indicated that Babussalam, Langkat has certain aspects of religious commodification. The components of commercialization include honouring intellectuals and requesting favours, or tabarruk. According to the Qur’an, the practice of commercializing religion is acceptable because no verses condemn the actions of the residents of Babussalam village.